Peran Membaca dalam Meningkatkan Kemampuan Berpikir Kritis di Kalangan Mahasiswa - Safira Nur Rahma; Fira Deyanti; Mahmudah Fitriyah (Institut Nalanda, 2024)
Critical thinking is a necessity in thinking, but the problem is that not everyone is able to think critically. In this research, researchers used reading activities as a way to realize critical thinking skills. Using the literature study method, this research was then carried out to strengthen the analysis that reading is the most magical key to being able to think critically through step by step in its efforts. Steps that can be taken from reading are to stimulate brain cells so they get used to thinking, foster creativity, and also increase vocabulary.